Bauran Pemasaran Tentang Konsep Apotek Modern Serta Strategi Pemasarannya - Welfin Dysyandi; Wahono Sumaryono; Sri Widyastuti; Henky Lesmana (JRB-Jurnal Riset Bisnis, 2019)
Pharmacy as the main type of distribution facility is still in great demand by investors. However, Jaminan Kesehatan Nasional (JKN) has the effect of decreasing turnover in some conventional pharmacies so that many pharmacies are closed. A pharmacy with a modern concept is expected to be an exit strategy of that problem. The purpose of this research is to find out and describe the concept of modern pharmacy according to the perceptions of respondents in DKI Jakarta province and its marketing strategy using the marketing mix concept. This research is a descriptive exploratory research by interviewing 100 respondents who have visited the pharmacy using a questionnaire. Data from interviews were analyzed using statistical software. The results showed that 98% of respondents agreed with the existence of a modern pharmacy concept. Modern pharmacy concepts that can be accepted by respondents are pharmacies that sell complete products, prices compete with surrounding pharmacies, locations close to housing or offices, friendly employees, fast and easy service processes, frequent promotions and social services in the community and a waiting room spacious and comfortable. The right marketing strategy for modern pharmacies is to prioritize excellent service and carry out vigorous promotions on online media and collaborate with private offices, government and universities in DKI Jakarta province.